The Influence of the 360-Degree Feedback System on Employee Performance and Career Development in Technology Companies in Indonesia - Loso Judijanto; Hesri Mintawati (Eastasouth Institute, 2025)
This study investigates the impact of the 360-degree feedback system on employee performance and career development in technology companies in Indonesia. Using a quantitative approach with a sample of 130 employees, data were collected through a structured questionnaire and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results demonstrate that 360-degree feedback has a significant positive effect on both employee performance and career development. Employees who receive feedback from multiple sources, including supervisors, peers, and subordinates, are better able to identify their strengths and areas for improvement, thereby enhancing work outcomes and preparing for career advancement. These findings contribute to existing literature by providing empirical evidence from the Indonesian technology sector, highlighting the system’s effectiveness in a culturally diverse context. Practically, the study suggests that organizations should integrate 360-degree feedback into their performance management and career development frameworks to foster employee growth and organizational competitiveness.